Overanticoagulation Associated with Combined Use of Antibacterial Drugs and Acenocoumarol or Phenprocoumon Anticoagulants - Visser, Loes E.; Penning-van Beest, Fernie J. A.; Kasbergen, A. A. Harrie; De Smet, Peter A. G. M.; Vulto, Arnold G.; Hofman, Albert; Stricker, Bruno H. Ch. (Thrombosis and Haemostasis, 2002)
Several case reports associated combined use of coumarins and antibacterial drugs with overanticoagulation. Despite the fact that these drugs are frequently prescribed concurrently, there is little quantitative information on the risks of such complications.To study which antibacterial drugs are associated with overanticoagulation during therapy with coumarins.Population-based cohort study in a sample of the Rotterdam Study.All patients who were treated with acenocoumarol or phenprocoumon in the study period from April 1, 1991 through December 31, 1998 and for whom INR data were available.Patients were followed until an INR 2: 6.0, the end of their treatment, death or end of the study period. Proportional hazards regression analysis was used to estimate the risk of an INR 2: 6.0 in relation to concomitant use of an oral anticoagulant and antibacterial drugs after adjustment for several potentially confounding factors such as age, gender, hepatic dysfunction, malignancies, and heart failure.Of the 1124 patients in the cohort, 351 developed an INR 2: 6.0. The incidence rate was 6.9 per 10,000 treatment days. Sulfamethoxazole combined with trimethoprim most strongly increased the risk of overanticoagulation with an adjusted relative risk of 20.1 (95% CI: 10.7-37.9). Stratification showed that the induction period of overanticoagulation varied between different antibacterial drugs.In this study among outpatients of an anticoagulation clinic using acenocoumarol or phenprocoumon, several antibacterial drugs strongly increased the risk of overanticoagulation. Awareness of these drug interactions and more frequent monitoring of INR values during the initial stages of antibacterial drug therapy are warranted to minimize the risk of bleeding complications.
Keywords: Acenocoumarol; phenprocoumon; anticoagulants